Neutrophil-Lymphocyte Ratio, Platelet Lymphocyte Ratio, And Carcinoembryonic Antigen Relationship With Survival In Non-Small Cell Lung Cancer Patients - Haryati Haryati; Ayudiah Puspita Mayasari; Farida Heriyani (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Inflammation is crucial to cancer development. A complete blood count is standard patient testing. Thus, inflammatory biomarkers like neutrophil-lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR) may predict lung cancer prognosis. Serum carcinoembryonic antigen (CEA) is the main predictive marker of most studies. Elevated NLR, PLR, and CEA levels are frequently associated with poorer overall survival in NSCLC patients. A retrospective cross-sectional study included 50 NSCLC medical records patients from Ulin Regional South Kalimantan Hospital. NLR, PLR, and CEA baseline peripheral blood individuals were investigated for NSCLC overall survival (OS). Patients are separated by OS mean into two groups. Mann-Whitney compared variables. The ROC curve and AUC were used to evaluate the above indicators' prognostic value. The mean of OS was 6 months. NLR, PLR, and CEA patients in ≤ 6 months had higher median values compared to > 6 months groups (8.73 vs. 4.3; 301.23 vs. 217.81; and 106 vs. 27.87). Survival was significantly associated with NLR and CEA (p-values 0.010 and 0.011). NLR >5.90 with AUC 0.725 (sensitivity 63.6%, specificity 29.4%) and CEA >41.39 ng/mL with AUC 0.722 (sensitivity 72.7%, specificity 29.4%). Parallel tests of NLR and CEA testing increased sensitivity and specificity (75.8%, 70.6%). This study revealed that elevated NLR and CEA are associated with patient survival, and monitoring both markers enhances survival prediction accuracy. It can improve insight into disease progression and adjust the therapeutic approach for NSCLC patients.